ROBOTIC-ASSISTED NEUROSURGERY: TECHNOLOGICAL INNOVATIONS, PRECISION ENHANCEMENT, AND FUTURE CLINICAL IMPACT IN BRAIN SURGERY (Global Conference on Medical and Health Sciences, 2026)
Robotic-assisted neurosurgery has emerged as a transformative advancement in modern surgical practice, offering enhanced precision, stability, and reproducibility in complex brain procedures. By integrating robotic systems with advanced imaging and navigation technologies, neurosurgeons can achieve greater accuracy in tumor resection, stereotactic interventions, and minimally invasive procedures.
Keywords: Robotic surgery; Neurosurgery; Brain tumor; Surgical precision; Minimally invasive surgery; Neurotechnology; Artificial intelligence; Surgical robotics; Clinical outcomes; Innovation